2007
DOI: 10.1111/j.1467-8691.2007.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Innovation and Performance Management of SME Clusters

Abstract: Continuous innovation and performance measurement methods and tools have been applied in companies as a means to develop improvement actions related to strategic objectives and to monitor results so as to give feedback for further action. However, continuous innovation and performance measurement methods and tools can also be applied to manage performance of a cluster of firms. After a brief review of continuous innovation and the concept of collective efficiency of a cluster, this paper presents a conceptual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 16 publications
(21 reference statements)
0
26
0
15
Order By: Relevance
“…No entanto, argumenta-se na literatura que a AD dessas organizações é um passo importante para a consolidação da rede, para trazer transparência ao processo decisório, para aumentar a confiança entre os parceiros, reforçar a competitividade e aumentar a eficiência coletiva (CARPINETTI, GEROLAMO e GALDÁMEZ, 2007;.…”
Section: Referencial Teóricounclassified
“…No entanto, argumenta-se na literatura que a AD dessas organizações é um passo importante para a consolidação da rede, para trazer transparência ao processo decisório, para aumentar a confiança entre os parceiros, reforçar a competitividade e aumentar a eficiência coletiva (CARPINETTI, GEROLAMO e GALDÁMEZ, 2007;.…”
Section: Referencial Teóricounclassified
“…The ability to generate innovations is facilitated through the specialization of socioeconomic environments and intensified as they generate interdependence between the various actors, producers, and users of goods, services, and technologies (Cassiolato & Szapiro, 2002;Carpinetti et al, 2007). Consequently, companies in a cluster are able to acquire components and services faster, which facilitate innovation due to the lower cost of experimentation and the reduced financial cost of innovation.…”
Section: Innovationmentioning
confidence: 99%
“…Incentive mechanism refers to a particular method or management system, which maximizes employees' commitment to organizations or work. Empirical studies also showed that the motivation of knowledgable workers such as rewards, recognition, work freedom, cooperative team, work challenge and pressure [45], cooperative trust, participation in decision, compensation, and broad career path [46], the goal-oriented compensation system, and way a team is organized can positively influence innovation performance [27].…”
Section: The Influence Of Incentive Mechanisms On Sustainable Innovationmentioning
confidence: 99%